Fabrication of 2D/2D BiOBr/g-C3N4 with efficient photocatalytic activity and clarification of its mechanism. Issue 33 (10th August 2022) - Lei, Jian; Gu, Xiaomeng; Xiao, Peipei; Ding, Guangzhu; Yang, Yang; Fu, Xianliang; Long, Baihua; Chen, Shifu; Meng, Sugang
Abstract : 2D/2D BOB/CN is applied for NFA degradation for the first time with high efficiency and stability, and the charge separation mechanism is demonstrated by EPR, in situ XPS and theoretical calculations. Abstract : Precise regulation of photoexcited charge carriers for separation and transportation is a core requirement for practical application in the photocatalysis field. Herein, a 2D/2D BiOBr/g-C3 N4 heterojunction is prepared by a self-assembly method and exhibits enhanced and stable activity for photocatalytic degradation of bisphenol A (BPA) and norfloxacin (NFA) under visible light. Compared to pure g-C3 N4, the kinetic constants of BPA and NFA degradation over BiOBr/g-C3 N4 are enhanced by about 14.74 and 4.01 times, respectively. The separation and transportation mechanism for the photoexcited charge carriers is clarified by electron paramagnetic resonance (EPR), in situ X-ray photoelectron spectroscopy ( in situ XPS), and theoretical calculations. The results show that BiOBr/g-C3 N4 exhibits the feature of a relative p–n junction, in which the charges photoexcited on BiOBr/g-C3 N4 with high redox potentials can be kept and spatially separated. Moreover, the built-in electric field with the direction of g-C3 N4 → BiOBr and the opportune band curvature provide the driving force for charge separation and transportation. Additionally, BPA and NFA degradation intermediates are also detected by liquid chromatography-mass spectrometry. It is of great significance to fabricate efficient photocatalysts for environmental purification and other targeted reactions.